Taxonomia e distribuição do gênero Lucifer (Decapoda, Sergestoidea) na costa central brasileira - Cardoso, Irene Azevedo (2002)
The genus Lucifer Thompson, 1829 comprises seven species, two are registered on the Brazilian coast: Lucifer faxoni Borradaile, 1915 and Lucifer typus Milne Edwards, 1837. The material for this study was obtained from two oceanographic cruises realized along the Brazilian central coast, as part of the REVIZEE (Levantamento dos Recursos Vivos da Zona Econômica Exclusiva Brasileira) project. Lucifer faxoni and L. typus were identified and separated in five classes: zoea, mysis, juveniles, adult males and females. The densities for each class, in each station of the two different cruises were calculated. These species presents different distribution patterns. Lucifer faxoni occurred in high frequency and abundance in Coastal Water and L. typus occurred in low frequency and abundance in Tropical Water and mixed waters. Larvae occurred in higher densities in Coastal Water. The highest densities of L. faxoni and larvae occurred on Central South Atlantic Water inflow at surface area (south of Espírito Santo and north of Rio de Janeiro). Male, female and juvenile variations are redescribed. A key and a catalogue of all Lucifer species are given.